Distribuição fitogeográfica de Parodia horstii (F. Ritter) N. P. Taylor (Cactoideae, Cactaceae) na região central do Rio Grande do Sul - Pontes, Rodrigo Corrêa (2021)
The landscape of Rio Grande do Sul presents a mixture of floristic elements present in its most varied environments. Among these, the Cactaceae family, with few scientific knowledge about distribution patterns at the species level. In order to contribute to this question, the following research had as the main objective to identify and characterize populations of Parodia horstii (F. Ritter) N. P. Taylor (Cactoideae, Cactaceae) in the central region of Rio Grande do Sul, in an attempt to relate the presence of the taxon in the study area with physical variables of geological, geomorphological and microclimatic order. To answer the objectives, fieldwork was carried out to identify populations in situ, to obtain primary data about ecology and to collect microclimatic data, which were organized and analyzed later. The delimitation of the study area was established according to the frequency of rocky outcrops and escarpments, isolated hills and dissected valleys, suitable environments for the establishment of cacti.The object area under research is located in the central region of Rio Grande do Sul, between the geographic coordinates at 29º 00 ' and 29º 45' South Latitude and 52º 45 'and 54º 45' West Longitude, with a minimum altitude of 28 meters and maximum altitude of 673 meters.The research was developed from primary data collected according to in situ observations and also through a bibliographic survey, where the conceptual framework of this thesis was established, supporting approaches and the characterization of the landscape in the study area. Regarding the methodology, the hypothetical-deductive method was adopted, as it is believed to allow a closer approximation of reality to the research developed. Based on the fundamentals of South American Refuge Theory, phytogeographic models of the Southern Cone and studies related to the theme, inferences were made in order to link the taxon with physical variables in the study area. It was also sought to identify and describe the imminent anthropic threats, when they exist. In an attempt to better understand the dynamics of the taxon's paleodistribution, a hypothetical scenario was outlined, based on information available in the scientific literature. Parodia horstii (F. Ritter) N. P. Taylor (Cactoideae, Cactaceae) was identified in twenty-two populations, plotted on thematic maps, for a better understanding of its geographic distribution dynamic. It can be concluded, the species obeys geological (lithology) and geomorphological (slope orientation) factors. However, with regard to microclimatic aspects, it is not possible to establish a direct relationship. According to the information collected, it is inferred that this endemic element of the regional flora has a limited distribution due to the characteristics present in relief sectors. In this way, since paleoclimatic events that occurred in the Late Pleistocene in Quaternary, the taxon continues to resist in form of islands, remaining in the current landscape.